Review of the Early Diagnoses and Assessment of Rejection in Vascularized Composite Allotransplantation - Ravi Starzl; Gerald Brandacher; W. P. Andrew Lee; Jaime Carbonell; Wensheng Zhang; Jonas Schnider; Vijay Gorantla; Stefan Schneeberger; Xin Xiao Zheng (Clinical and Developmental Immunology, 2013)
The emerging field of vascular composite allotransplantation (VCA) has become a clinical reality. Building upon cutting edge understandings of transplant surgery and immunology, complex grafts such as hands and faces can now be transplanted with success. Many of the challenges that have historically been limiting factors in transplantation, such as rejection and the morbidity of immunosuppression, remain challenges in VCA. Because of the accessibility of most VCA grafts, and the highly immunogenic nature of the skin in particular, VCA has become the focal point for cross-disciplinary approaches to developing novel approaches for some of the most challenging immunological problems in transplantation, particularly the early diagnoses and assessment of rejection. This paper provides a historically oriented introduction to the field of organ transplantation and the evolution of VCA.